PENGARUH KUALITAS LAYANAN LAKU PANDAI (BRILINK) TERHADAP KEPUASAN NASABAH DALAM BERTRANSAKSI KEUANGAN - Dila Damayanti; Nurseto Purnomo Putro; Selamat Riauwanto (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to determine the effect of tangible, reliability, responsiveness, empathy and Assurance on customer satisfaction in financial transactions in the Bantul area. The population in this study were BRI Bank customers, with 90 respondents as samples. The sampling technique used purposive sampling technique with the criteria of BRI Bank customers in the Bantul Regency area and BRI Bank customers in the Bantul Regency area who used the I Smart BRILink service. The data analysis technique used in this research is multiple linear regression analysis. The results of this study show that tangible has no effect on customer satisfaction, reliability has no effect on customer satisfaction, responsiveness has a positive effect on customer satisfaction, empathy has a positive effect on customer satisfaction, and assurance has no effect on customer satisfaction.